Research Mapping of Domestic Violence and Governance (Journal of Namibian Studies : History Politics Culture, 2023)
The purpose of this study is to discuss a historical bibliometric overview of research with the keywords "domestic violence" and "governance" compiled in the Scopus database as well as to analyse the content of the 10 most cited articles. The method of this research is bibliography analysis of data, processed using VOSviewer to determine co-authorship, co-occurrence, citation, and bibliography coupling. From the results, it can be seen that the first publication was in 2003 [1] and that the ten most cited documents discuss the phenomena of "domestic violence" and "governance" not only in developing and low-income countries, as well as conflict-affected countries, but also in developed countries. A holistic and sustainable approach is needed to create significant social change in addressing this issue. In addition, Opportunities for further publications include those related to the concept of "coordination" or "networks".